Can VO2max be accurately estimated using exercise-duration based prediction equations and a nomogram? - Adam Natalie A.; Duquette Adriana M. (Sciendo, 2024)
Study aim: The purpose of this study was to examine a large cohort of young Canadian adults to determine if exercise time from a maximal Bruce Treadmill Protocol could accurately predict measured VO2max values by inputting the total exercise time into prediction equations and a nomogram.